Crystallinity and impact strength improvement of wood-polylactic acid biocomposites produced by rotational and compression molding - Pérez-Fonseca, Aida; Ramírez-Herrera, Verónica; Fuentes-Talavera, Francisco; Rodrigue, Denis; Silva-Guzmán, José; Robledo-Ortíz, Jorge (Maderas. Ciencia y Tecnología, 2021)
Polylactic acid is one of the most used biopolymers due to its overall properties and biodegradability. Nevertheless, polylactic acid has important drawbacks such as brittleness, low thermal stability, and higher cost than most commodity polymers. In order to overcome those disadvantages without compromising biodegradability, the addition of wood particles and thermal annealing on the crystallinity and impact strength of wood-polylactic acid biocomposites were studied. The samples were prepared by compression and rotational molding using two different wood particles: white ash and tzalam. The results showed that thermal annealing at 100 °C, 40 minutes, increased the crystallinity up to 60 % and also improved the thermal stability of polylactic acid and its biocomposites as determined via dynamic mechanical analysis. The specimens not exposed to thermal annealing exhibited important storage modulus loss above 60 °C, which mostly disappeared with the thermal treatment. Furthermore, the impact strength was substantially increased by the thermal treatment. Additionally, accelerated weathering tests showed that the thermally annealed samples had better dimensional stability growing their potential applications over a wider range of conditions.